Long Noncoding RNA LINC-PINT Suppresses Cell Proliferation, Invasion, and EMT by Blocking Wnt/β-Catenin Signaling in Glioblastoma - Zhu, Hanshuo; Chen, Zheng; Shen, Lin; Tang, Tianchi; Yang, Min; Zheng, Xuesheng (Frontiers in Pharmacology, 2021)
Background: Glioblastoma (GBM) represents the most aggressive glioma with high invasive potential. Recent studies proved the involvement of epithelial-mesenchymal transition (EMT) process in increasing the malignancy and invasiveness of GBM. LncRNAs have been verified to play pivotal roles in human disease including GBM. However, the molecular mechanisms of lncRNA-mediated EMT in GBM remain largely unknown. LINC-PINT, a LncRNA which has never been studied in GBM before, was predicted to be negatively associated with EMT in GBM. This study aimed to explore the biological function and the EMT relevance of LINC-PINT in GBM and further explore the molecular mechanism. Methods: The bioinformatic prediction data of LINC-PINT in GBM was derived from The Cancer Genome Atlas (TCGA) database by R software and GEPIA website. qRT-PCR assay was performed to detect the expression level of LINC-PINT in GBM cell lines. Cell counting kit-8 (CCK8), clone formation, transwell, and wound healing assays were performed to determine the biological function of LINC-PINT in vivo. Tumor xenograft experiment and tumor peritoneal metastasis experiments were performed to verify the in vivo function. Western blot and immunofluorescence staining assays were carried out to detect the relevance of LINC-PINT with EMT and Wnt/β-catenin signaling. Rescue assays were performed to check the regulation mechanism of LINC-PINT/Wnt signaling/EMT axis in GBM. Results: LINC-PINT was downregulated in GBM cell lines. LINC-PINT suppressed cell progression, invasion, and EMT in GBM. LINC-PINT blocked Wnt/β-catenin signaling in GBM. Conclusion: LINC-PINT suppressed cell proliferation, invasion, and EMT by blocking Wnt/β-catenin signaling in GBM.